(untitled) (European Journal of Education and Psychology, 2010)
Learning activities may affect specific aspects of certain disciplines and an effort to increase motivation in our students is needed. This study deals with an activity in which students handle content close to two Psychology subjects (Personality and Social Psychology). The main aim was to relate concepts that are approach from the two disciplines by different, but similar, points of view and to increase students’ motivation by their active implication in a learning activity. Students conducted real research which managed theoretical content of these two courses. Two groups of students (experimental and control) participated in this study (N=286). Our results show a significant increase of the participants in this experiment in academic performance in both courses. Participants in this activity have achieved better final grades than their non-participant peers (in both disciplines), and also improved their own performance, enhancing their grades in comparison with the ones they obtained in the first semester. Finally, our results show that there is an increase in performance with these methodologies, even when the subjective assessment of students about their motivation is not so positive.